Exploring the Impact of Gamification on English Language Learning for Students in Asia Countries: A systematic review - Supasa, Aprilia Yunda; Ramadhani, Meutya Rizki; Ningrum, Fatma Setya; Hamuddin, Budianto (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
This study explores the effectiveness of gamification in English language learning in Asian countries, aiming to identify best practices and challenges in its integration. Although gamification has been widely acknowledged for enhancing student engagement and motivation, its impact on improving actual language proficiency remains uncertain, especially in the diverse educational contexts of Asia. Through a systematic review of literature published from 2019 to 2024, this research addresses gaps in existing studies, particularly those focusing on gamification within Asian educational systems. The review adheres to PRISMA guidelines, and data were gathered using the Publish or Perish tool, which identified 1,053 studies based on keywords such as